Nutritional quality of milk curd by adding avocado extract (Persea americana, mill) using gombong bamboo (Gigantochloa verticilata) - Putri Theresia Pandiangan; Tri Hesti Wahyuni; Hamdan . (Universitas Sumatera Utara, 2019)
Curd is a traditional fermented buffalo milk from West Sumatra.Fermentation in curd making occurs spontaneously, meaning thatfermentation occurs naturally without the addition of a starter. This studyaims to determine the nutritional content of cow milk curd with the additionof avocado extract (Persea americana, Mill) various levels using Gombongbamboo (Gigantochloa verticilata).This research was conducted at the Analogy and Physiology Laboratory ofthe Faculty of Agriculture, University of North Sumatra in November 2018-December 2018. The design used in this study was a completelyrandomized design (CRD) with 5 treatments and 4 replications. Theparameters analyzed were Protein, Fat, and pH. The results showed thatcow milk curd with the addition of avocado (Persea americana, Mill)extract various levels using Gombong bamboo (Gigantochloa verticilata)significantly had different effects on the nutritional value of protein, fat andpH. From the nutritional value studied, the highest protein: P1 7.57% withthe addition of avocado fruit extract (Persea americana, Mill) 6%, fataverage: P1 7.08% with the addition of avocado fruit extract (Perseaamericana, Mill) 6%, pH: P4 5.30% with the addition of avocado fruitextract (Persea americana, Mill) 24%.